Ensuring patient access to affordable cancer drugs : workshop summary - Nass, Sharyl J.; Patlak, Margie (The National Academies Press, 2014)
In recent years, patients' out-of-pocket costs for cancer care have been rising rapidly. These costs include health insurance deductibles, coinsurance, and copayments for covered services, as well as services that are not covered by insurance. Many cancer patients are especially vulnerable financially because their illness and/or treatment impedes their ability to work, with some patients losing employment altogether. Even with insurance, cancer patients often experience financial hardships, such as going into debt, depleting all assets to pay for cancer treatment, and personal bankruptcy. Although many elements contribute to the cost of cancer care, one important component is the cost of new cancer drugs, which has been escalating rapidly in recent years. To explore the issue of cancer drug costs and patient access to affordable, appropriate drug therapies, the Institute of Medicine's National Cancer Policy Forum convened a workshop on ensuring patient access to affordable cancer drugs in June 2014. Affordability was considered from both individual and societal perspectives. The workshop featured discussion panels as well as invited presentations from clinicians, researchers, representatives from the health insurance and pharmaceutical industries, and patient advocates. Ensuring Patient Access to Affordable Cancer Drugs summarizes the presentation and discussion of the workshop.